2008
DOI: 10.1016/j.matchemphys.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of methyl orange with W-doped TiO2 synthesized by a hydrothermal method

Abstract: a b s t r a c tNanosized W-doped TiO 2 photocatalysts were synthesized by a simple hydrothermal method, and characterized by energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), transmission electron microscopy (TEM) and BET surface area analyzer. The photocatalytic activity of undoped TiO 2 and Wdoped TiO 2 photocatalysts was evaluated by the photocatalytic oxidation degradation of methyl orange in aqueous solution. The results show that the photocatalytic activity of the W-doped TiO 2 photoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 24 publications
(23 reference statements)
1
19
0
1
Order By: Relevance
“…Therefore, when the MO solution pH value is below the PZC, the MO anions should be readily adsorbed on the surfaces of nano-sized ZnO particles. As is described by H. Tian et al [1], the photocatalytic degradation efficiency of MO solutions with nano-sized TiO 2 catalysts changes with the temperature variation of the MO solutions. Hence, the effect of MO solution temperature on the degradation efficiency of MO catalyzed by ZnO nano-particles was also discussed in the range from 20 to 70˚C at 10˚C intervals in this study.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, when the MO solution pH value is below the PZC, the MO anions should be readily adsorbed on the surfaces of nano-sized ZnO particles. As is described by H. Tian et al [1], the photocatalytic degradation efficiency of MO solutions with nano-sized TiO 2 catalysts changes with the temperature variation of the MO solutions. Hence, the effect of MO solution temperature on the degradation efficiency of MO catalyzed by ZnO nano-particles was also discussed in the range from 20 to 70˚C at 10˚C intervals in this study.…”
Section: Resultsmentioning
confidence: 88%
“…Semiconductor photocatalysts such as TiO 2 and ZnO nano-particles have attracted much attention in recent years due to their various applications to the photocatalytic degradation of organic pollutants in water and air and dye sensitized photovoltaic solar cell [1][2][3]. Among these semiconductor photocatalysts, TiO 2 is the most commonly used owing to its stable, harmless and inexpensive properties.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic decomposition of various organic compounds in industrial wastewater has been extensively studied, since the pollutants can be oxidized quickly and non-selectively [1][2][3][4][5][6][7][8]. Among various semiconductors, titanium oxide (TiO 2 ) has been employed as a typical photocatalyst for both fundamental research and practical applications owing to its excellent stability and high photoactivity under ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important applicabilities of nano-ZnO is based on its photocatalytic activity which occurs under ultraviolet light excitation [42][43][44][45][46]. In 2008, Ma et al [47] reported that the catalytic activity of TiO 2 in photocatalytic degradation of methyl orange can be highly improved by doping with tungsten. They attributed this result to the help of the doped W in trapping of photogenerated electrons and the enhancement of the surface acidity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%